Synthesis and cytotoxicity study of gold(III) porphyrin complexes and their derivative in breast cancer cells - Tossapon Phromsatit; Premjit Arpornmaeklong; Yuki Shirosaki; Thapong Teerawatananond; Jundee Rabablert; Supakorn Boonyuen (Journal of Saudi Chemical Society, 2021)
Gold(III) [Au(III)] complexes exhibit potential anticancer activities. A series of Au(III) porphyrin complexes containing different meso-substituent groups (phenyl, methoxyphenyl, butyloxyphenyl, octyloxyphenyl, and decyloxyphenyl) was synthesized. The synthesized compounds were characterized using mass spectrometry, infrared spectroscopy, UV–visible and fluorescence spectroscopy, and electron paramagnetic resonance spectroscopy. Moreover, the in vitro cytotoxicity of these Au(III) porphyrin complexes was investigated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide surrogate viability assay on an MCF7 human breast cancer cell line. The Au(III) complexes with 5,10,15,20-tetraphenylporphyrin (AuTPP) and 5,10,15,20-tetrakis(4-methyloxyphenyl)porphyrin (AuTOMPP) demonstrated high anticancer activity with IC50 values against MCF7 cells at 4.30 and 25.35 µM, respectively. The toxicity of the Au(III) porphyrin complexes against the LLC-MK2 rhesus monkey kidney epithelial cell line, a representative normal cell line, was investigated. All the tested Au(III) porphyrin complexes were non-cytotoxic in LLC-MK2 cells. For AuTPP, more than 80% LLC-MK2 cell viability was observed at concentrations lower than 5 μM.
Keywords: Metal complexes synthesis and properties; Porphyrin and Phthalocyanine Chemistry; Synthesis and Characterization of Heterocyclic Compounds